Pulmonary microbial spectrum of Burkholderia multivorans infection identified by metagenomic sequencing - Xu, Hui; Zhang, Ruixue; Zhang, Xiaoxue; Zhang, Zhi; Feng, Yingmei; Lin, Lianjun (Frontiers in Medicine, 2025)
PurposeBurkholderia multivorans, a Gram-negative bacterium, often infect patients with severe immunocompromised and cystic fibrosis. B. multivorans infection is challenging to treat due to its ability to disrupt the action of multiple antimicrobial agents through intrinsic and acquired resistance mechanisms. A better understanding of the pulmonary microbial spectrum of B. multivorans infection is crucial for the prevention and treatment of B. multivorans.Case presentationThis case series reviewed the respiratory microbiome structure and alternations during the treatment of B. multivorans infection through metagenomic next-generation sequencing (mNGS). Analysis of mNGS data of 19 pharyngeal secretion samples collected from the 3 COVID-19 patients at different time points showed that the relative abundance of B. multivorans was fluctuated and eventually increased, indicating the possible development of drug resistance. A total of 40 antibiotic-resistant genes (ARGs) were detected. Significantly, the levels of CEOA, CEOB, and OPCM were consistent with the trends in the relative abundance of B. multivorans. Besides, we described nine previously uncharacterized non-synonymous mutations in PenA of B. multivorans. These mutations lead to amino acid changes Thr32Ala, Ala43Ser, Gln105Arg, Asn202Ser, Gln219Arg, Gly241Ala, Val259Ala, Thr279Ala, and Ser298Ile that may associate with resistance to β-lactam antibiotics.ConclusionThis report shed light on the importance of rapidly diagnosis and treatment of B. multivorans infection. mNGS serve as a powerful microbial detection tool that provides a comprehensive, sensitive, and rapid method for pathogen detection and drug resistance analysis.